Flatliners (2017) [videorecording (DVD)] - Page, Elliot, 1987-; Luna, Diego, 1979-; Dobrev, Nina, 1989- (Sony Pictures Home Entertainment, 2017)
Five medical students, obsessed by what lies beyond the confines of life, embark on a daring experiment: by stopping their hearts for short periods, each triggers a near-death experience, giving them a firsthand account of the afterlife.